2015
DOI: 10.1590/1678-4499.0133
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos fisiológicos e qualidade de mudas da pimenteira em resposta ao vigor e condicionamento das sementes

Abstract: A pimenta é um fruto do gênero Capsicum, bastante utilizada na culinária como tempero. Objetivou-se com este trabalho verificar o efeito do condicionamento fisiológico em sementes de Capsicum frutescens, e sobre as mudas obtidas das sementes condicionadas. O delineamento experimental foi o inteiramente casualizado em esquema fatorial 2x6, designado por: qualidade fisiológica das sementes (vigor acima e abaixo) e cinco agentes no condicionamento fisiológico (água, nitrato de potássio a 0,2%, nitrato de cálcio a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 11 publications
1
22
0
5
Order By: Relevance
“…As observed by Batista et al (2015), high-vigor seeds primed with KNO 3 and Ca(NO 3 ) 2 favor plant height and produce C. frutescens seedlings with higher dry mass than the control. CONCLUSIONS 1.…”
Section: Resultsmentioning
confidence: 57%
“…As observed by Batista et al (2015), high-vigor seeds primed with KNO 3 and Ca(NO 3 ) 2 favor plant height and produce C. frutescens seedlings with higher dry mass than the control. CONCLUSIONS 1.…”
Section: Resultsmentioning
confidence: 57%
“…15 In Capsicum annuum Kikuti et al (2005) showed that conditioning with KNO 3 is effective to improve seed performance and the increase of exposure time to the priming solutions favors the process of ex vitro germination of sweet pepper. Batista et al (2015)demonstrated that priming for the ex vitro germination of Capsicumfrutescens is active in the emergence speed and the KNO 3 usage increases the seedlings dry weight, however the seeds quality is related to the germination treatments results.…”
Section: Discussionmentioning
confidence: 99%
“…KNO 3 ) as indicated in studies on the ex vitro seed germination of several species including Capsicum and that have shown variable germination patterns and seedling emergence (Aloui, Souguir, & Hannachi, 2014;Batista et al, 2015;Cortez-Baheza et al, 2011;Maiti, Rajkumar, Jagan, Pramanik, & Vidyasagar, 2013;Smith & Cobb, 1991). Among the most diverse treatments suggested in the literature (water, NaCl, CaCl 2 , KCl, PEG, KNO 3 , GA 3 , e.g.)…”
Section: Discussionmentioning
confidence: 99%
“…The priming of tomato seeds with CaCl 2 and KNO 3 solution was efficient to improve the seedling growth under salinity conditions (Ebrahimi et al, 2014). Similarly, Batista et al (2015) reported that the priming with KNO 3 and Ca (NO 3 ) 2 resulted in greater growth of pepper (C. frutescens) seedlings. However, the priming of cucumber seeds with potassium nitrate showed little effect in improving the germination and growth rate of seedlings under salt stress conditions (Oliveira & Steiner, 2017).…”
Section: Introductionmentioning
confidence: 93%